PjBL-STEM Model in Mathematics Education: A Systematic Literature Review on Effectiveness, Differentiation, and Affective - Yusak Bien; I Nengah Suparta; I Gusti Putu Suharta; I Gusti Putu Sudiarta (Universitas Majalengka, 2026)
The changing landscape of 21st-century education demands that mathematics learning is no longer oriented towards procedural reproduction, but rather towards the development of higher-order thinking skills, contextual problem-solving, and students' affective engagement. The integration of Project-Based Learning (PjBL) based on Science, Technology, Engineering, and Mathematics (STEM) is seen as a potential pedagogical strategy to address these challenges. Although various studies report the effectiveness of PjBL-STEM on mathematics learning outcomes, studies that comprehensively integrate learning effectiveness, learning differentiation, and students' affective dimensions are still limited. This study aims to systematically examine the application of the STEM-based PjBL model in mathematics education with a focus on learning effectiveness, differentiation practices, and students' affective dimensions. This study uses a Systematic Literature Review (SLR) approach with reference to the PRISMA guidelines. Articles were collected from Scopus, Web of Science, ScienceDirect, SpringerLink, and ERIC databases, with a publication range of 2015–2025. Twelve articles that met the criteria were analyzed using thematic content analysis and narrative synthesis. The review results show that STEM-based PjBL consistently has a positive impact on mathematical cognitive outcomes, problem-solving abilities, and 21st-century skills. However, learning differentiation strategies are generally not explicitly designed, and affective variables are often required as additional variables. These findings emphasize the need to develop integrative and inclusive PjBL-STEM designs that systematically consider diverse student characteristics.